1999
DOI: 10.1128/iai.67.8.4143-4148.1999
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CD4+T Cells and Gamma Interferon in Protective Immunity againstBabesia microtiInfection in Mice

Abstract: Babesia microti produces a self-limiting infection in mice, and recovered mice are resistant to reinfection. In the present study, the role of T cells in protective immunity against challenge infection was examined. BALB/c mice which recovered from primary infection showed strong protective immunity against challenge infection. In contrast, nude mice which failed to control the primary infection and were cured with an antibabesial drug did not show protection against challenge infection. Treatment of immune mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…Th1 cytokine responses are thought to dominate in B. microti infections-at least during acute infection [12]. IFN-g has been reported to have some role in the resolution of acute infection of mice infected with B. microti and to be involved in protection against other intracellular parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cytokine responses are thought to dominate in B. microti infections-at least during acute infection [12]. IFN-g has been reported to have some role in the resolution of acute infection of mice infected with B. microti and to be involved in protection against other intracellular parasites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients who suffer from lymphoproliferative disorders of the B cell compartment and are treated with regimens that deplete B cells also are at risk for persistent or relapsing babesiosis, [55] suggesting an important role for B cells in host resistance. However, studies of B. microti infection in mice do not provide strong evidence of a role for B cells and immunoglobulins in host resistance, [82,[95][96][97] implying that additional immune dysfunction is required for symptomatic babesiosis to develop in patients with B cell proliferative disorders.…”
Section: Host Immune Responsementioning
confidence: 99%
“…The requirement for IFN-γ is less clear. One study using IFN-γ knockout mice showed delayed but eventual resolution of disease caused by B. microti (21), whereas a separate study showed no protection against challenge with this parasite in mice depleted of IFN-γ by specific antibody treatment (20). Differences may be related to the use of different parasite strains.…”
Section: Mouse Models Of Immunity To Babesiamentioning
confidence: 99%